Suggested Model for activating the roleof the regulators for the auditing professionin achieving quality audit: دراسة تطبيقية في الشركة العامة للصناعات النسيجية- واسط (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The modern business environment Witness tremendous.These developments result from globalization of markets and economic and technological openness. Those developments resulting a heightened competition between economic units and higher the costs of their products and lower their functional characteristics. They do not take into account the response to the requirements of customers. This matter commit it to search for scientific methods to help it to cope with the happening changes and improve its competitive position, The current study acquired its importance by providing significance through by applicable integrated framework to reduce the costs of products. This reduction should be without compromising their quality by using the integration between Target Costing and Value Engineering with support Quality Function Deployment. Techniques of Target Costing and Value Engineering consider the most suitable formula for the management of costs and pricing of products and addition to increasing the capacity of economic units on the competition.